Referential and pragmatic-discourse properties of Lithuanian reference impersonals: 2sg-imp, 3-imp and ma/ta-imp - Mazzitelli, Lidia Federica (Kalbotyra, 2019)
In this paper I describe the semantics, pragmatics and the discourse functions of three Lithuanian agent-defocusing constructions, featuring the non-referential use of second person singular/third person verbal forms and the non-agreeing participial forms in ma/ta. These three constructions can all be defined as impersonal, in the broader sense of the word, as the agent (or the main participant, whatever its semantic role may be) is constructed as non-referential: I label them 2sg-imp, 3-imp and ma/ta-imp. My corpus consists of original Lithuanian texts (a short story and entries on an Internet forum) and of the Lithuanian translations of Antoine de Saint-Exupéry’s novella Le Petit Prince and J.K. Rowling’s Harry Potter and the Philosopher’s Stone. My analysis shows that 2sg-imp are preferably used to express generic agents (anyone) and 3-imp are preferably used to express referential indefinite agents (someone). while ma/ta-imp are referentially flexible. 2sg-imp are pragmatically marked in that they are used to express empathy between the speaker and the pool of potential referents; they are mostly used in specific discourse types, such as opinion statements and life drama situations. 3-imp are preferred in situations where the indefiniteness of the agent is relevant to the development of the narrative; ma/ta-imp are instead preferred when the agent is irrelevant, and the focus is on the event itself. The behavior of Lithuanian 2sg-imp, 3-imp and ma/ta-imp is consistent with the one already described for similar constructions in other European languages.
Keywords: impersonal constructions; semantics; pragmatics; ma/ta-participles; discourse analysis